Co-constructing stories with patients with heart failure to envision future remote care possibilities: a qualitative interview and sketching study - Wessel W. Nieuwenhuys; Hannah C. van Iterson; Jeroen A. A. van de Pol; Mayke M. C. J. van Leunen; Ignace L. J. de Lathauwer; Mathias Funk; Rong-Hao Liang; Hareld M. C. Kemps (Frontiers in Digital Health, 2026)
Introduction Although remote patient management (RPM) shows promise for improving chronic heart failure (HF) management, its effectiveness depends on technology acceptance, usability, and patient engagement. However, patients are often involved only after systems are implemented, limiting opportunities to align RPM with their needs. This study explored patients' expectations, wishes, and concerns regarding future RPM using participatory design methods to inform more patient-centred RPM. Methods Patients with HF using RPM were recruited from a Dutch hospital for individual, semi-structured interviews. We employed a co-constructing stories approach, inviting participants to imagine future scenarios of remote care. Guided by narrative prompts about potential developments in RPM, participants were encouraged to discuss how such technologies might shape their experiences. During the interviews, one researcher concurrently created sketches of the participants' answers, creating an evolving trace of the dialogue. The visual data were subsequently analysed using Annotated Visual Analysis to identify themes. Results Six patients were interviewed, producing 7 h of audio and 18 A3 pages of sketch notes. Four key themes emerged: Data Feedback, reflecting patients' desire to receive clear and constructive feedback that supports self-management beyond alert-based monitoring, to be able to take more responsibility for their health through RPM; Invasiveness, including camera-based monitoring or collection of non-medical data, was perceived as a barrier to adoption, although concerns were reduced when monitoring was clearly explained and considered proportional to disease severity; Adaptability and Integration highlighted the need for RPM to extend support beyond monitoring and to remain useful in daily life; Healthcare Provider contact emphasised that human interaction is irreplaceable, with empathy from healthcare professionals fostering trust in the system and patients' confidence in managing their health. Conclusion Inviting patients to reflect on remote care provided valuable insights into their needs and expectations for future RPM. Participatory design methodologies facilitated rich discussions about patients' experiences, needs, and expectations regarding future RPM. Patients emphasised RPM should be actionable, minimally invasive, adaptable to daily life, and complemented by human contact. This highlights the importance of socio-technical systems that empower self-management while maintaining professional support. These findings can guide more human-centred RPM designs for HF care.